The "AMA-Brazil" cooperative project: a nation-wide assessment of the clinical and epidemiological profile of AIDS-related deaths in Brazil in the antiretroviral treatment era Projeto cooperativo AMA-Brasil: um estudo nacional do perfil clinico e epidemiológico dos óbitos relacionados à AIDS na era da terapia antirretroviral - Maria Amelia de Sousa Mascena Veras; Manoel C. A. Ribeiro; Leda Fátima Jamal; Willi McFarland; Francisco Inácio Bastos; Karina Braga Ribeiro; Rita Barradas Barata; José Cassio de Moraes; Arthur L. Reingold (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The objective of this study was to assess the profile of AIDS-related deaths in the post antiretroviral therapy (ART) scale up period in Brazil. A case-control study was conducted including a nationally probabilistic sample of AIDS deaths and living controls. Data were abstracted from medical records and nation-wide databases of AIDS cases, mortality, ART care, and laboratory testing. Interrupted (adjusted odds ratio - AOR 4.35, 95%CI: 3.15-6.00) or no use of ART (AOR 2.39, 95%CI: 1.57-3.65) was the strongest predictor of death, followed by late diagnosis (AOR 3.95, 95%CI: 2.68-5.82). Criterion other than CD4 < 350 had a higher likelihood of death (AOR 1.65, 95%CI: 1.14-2.40). Not receiving recommended vaccines (AOR, 1.76, 95%CI: 1.21-2.56), presenting AIDS-related diseases (AOR 2.19, 95%CI: 1.22-3.93) and tuberculosis (AOR 1.50, 95%CI: 1.14-1.97) had higher odds of death. Being an injecting drug user (IDU) had a borderline association with higher odds of death, while homo/bisexual exposure showed a protective effect. Despite remarkable successes, Brazilians continue to die of AIDS in the post-ART scale up period. Many factors contributing to continued mortality are preventable Analisou-se o perfil clínico e epidemiológico dos óbitos relacionados à AIDS no período posterior à implementação da terapia antirretroviral (TARV) no Brasil, em um estudo caso-controle, com amostra representativa de óbitos por AIDS e de pessoas vivendo com AIDS, utilizando dados secundários. Abandono (odds ratio ajustada - AOR = 4,35, IC95%: 3,15-6,00) ou não uso da TARV (AOR = 2,39, IC95%: 1,57-3,65) foi o mais forte preditor de morte, seguido de diagnóstico tardio (AOR = 3,95, IC95%: 2,68-5,82). Critério de definição de AIDS que não o "CD4 < 350" esteve associado a uma maior probabilidade de morte (AOR = 1,65, IC95%: 1,14-2,40). Pacientes que não receberam vacinas recomendadas (AOR = 1,76, 95%CI: 1,21-2,56), apresentando doenças associadas à AIDS (AOR = 2,19, IC95%: 1,22-3,93) e com tuberculose (AOR = 1,50, IC95%: 1,14-1,97), tiveram maior risco de morte. A categoria de exposição UDI apresentou maior chance de óbito. Apesar do sucesso com as introduções precoces da TARV, brasileiros continuaram a morrer de AIDS no período posterior à implementação da terapia, e muitas das causas subjacentes a essa mortalidade são preveníveis.